Integration of Cultural Values On The Learning of Speaking Skills - Munirah Munirah (Eduvest - Journal of Universal Studies, 2022)
This paper aims to examine the value of local culture in learning speaking skills. Indonesian is a subject that develops learners' ability to communicate cultural values through behavior and the use of language in a variety of work-related contexts. Therefore, to be skilled in language with four skills, learners need an interesting learning process. Culture-based education is a viable alternative to improve the educational process and improve school literacy discourse. The power of culture aims to reduce the negativity of learner behavior. The value of local budaya is an important issue that should be studied in learning Social Geography. Facing this new requires various strategies including by adopting local cultural values in the learning process, especially learning speaking skills